UK banking supervision : evolution, practice, and issues - Gardener, Edward P. M. (London ; Boston : Allen & Unwin, 1986)
Part A of this book, by the editor provides a general background to regulation and UK bank supervision in particular. It sets the scene for the rest of the book. Part B comprises four invited papers on different aspects of the growth and operation of supervision in the UK. Part C looks generally at selected areas, like competition and the problems associated with setting supervisory objectives. Finally, parts D and E are devoted to specialist considerations of two fundamental areas of supervision, capital adequacy and deposit insurance.
Includes index.
Includes bibliographical references and index.
II 15/01/2019
Loans
Keywords: Banks and banking; United Kingdom